The Galileo Galilei Institute for Theoretical Physics in Arcetri - De Curtis, Stefania (Il Colle di Galileo, 2022)
The “Galileo Galilei Institute for Theoretical Physics” (GGI), the first European Institute dedicated to training and research in leading topics in theoretical physics, was founded on Arcetri hill in 2005. Housed in the “Garbasso” building, the former headquarters of the Institute of Physics in Florence, the GGI is a point of reference for the international scientific community.